UJI EFEK STIMULAN FRAKSI N-HEKSAN DAUN PEGAGAN (Centella asiatica (L.)Urban) - Nurma Suri; Subur Widodo; Mega Intan Yulianti (Program Studi Farmasi Universitas Tulang Bawang, 2021)
Abstract Current condition related to fulfilling stimulating in the societies is by energy drinks and vitamins which have side effects restless, nervous, tremor, and seizures. Alternative stimulant can derived from herbs. One of the plants has potention of stimulant is Centella asiatica. This study was to examine the effect of stimulant on fraction n-hexane of C.asiatica leaves. The simplisia of C.asiatica leaves was extracted with ethanol 70% using a maceration method. Thereafter, extract was fractionated using n-hexane. Phytochemical screening was carried out to determine the content of secondary metabolites in order to find out the potential utilization by testing the active compounds. Stimulant effect was evaluated using induced sleeping time, swimming endurance time, hanging time, and rotarod method with the dose 2.59 mg/KgBW, 5.185mg/KgBW, 10.37 mg/KgBW, and 15.55 mg/KgBW, caffeine as the positive control, and Na-CMC as the negative control. The phytochemical screening showed positive results for triterpenoids and alcaloid. All of the dose fraction n-hexane had effect stimulant however dose 5.185 mg/KgBW and 10.37 mg/KgBW had as same stimulant effect as positive control and dose15.55 mg/BW had higher stimulant effect. N-hexane fractionation of C.asiatica leaves demonstrated the presence of secondary metabolites with potential biological activities as stimulant. Keywords: Alkaloids, C. asiatica, Triterpenoids, Stimulants test